If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5p+9=2p-1
We simplify the equation to the form, which is simple to understand
5p+9=2p-1
We move all terms containing p to the left and all other terms to the right.
+5p-2p=-1-9
We simplify left and right side of the equation.
+3p=-10
We divide both sides of the equation by 3 to get p.
p=-3.33333333333
| Y=1.1*25+157 | | f=-2+4x+-2x^2 | | 2+x=2-2x | | 60(t-2)=30r | | -7x+3-9x= | | 85+(2x-5)= | | -3.4w=-22.1 | | 2=8(t)-4.9(t) | | 7x-[x-(2x+8)]=3x-7 | | 6x=9x-15 | | 2=8(t)-4.9(t)2 | | 3x+4y+6z=100 | | Y=1.1*40+157 | | 0.5a+(a-1)-(0.2a+10)=0.2a-(0.2a-28) | | 4x-7=6(x-3) | | 7(-6x+8)=-322 | | 1x-4=5 | | -30y+110=-12y+70 | | 0.5D-5=6 | | 55+(x+25)= | | x-35=28 | | (x+x+x+x+x+x+x)*.6*4.0=97.2 | | 55+32=25 | | 6b=6v-6b | | (x+x+x+x+x)*.6*4.0=97.2 | | 9w=45 | | 3w/2+7=10 | | 5x*.6*4.0=97.2 | | 5y-15=2y-16 | | 2-35= | | 4-4x=-3(x-2) | | 10-2(2*2)+8/4=g |